Pengaruh Orang Tua terhadap Perkembangan Anak dalam Interaksi Sosial - Flora.S, Dwi Elsi (TSAQOFAH, 2026)
The development of children’s social interaction is a crucial aspect in shaping personality and social adaptability; however, studies that specifically integrate the role of parents, parenting patterns, and the quality of family communication within the context of modern social life remain relatively limited. This study aimed to analyze the influence of the parental role on the development of social interaction among elementary school–aged children. A quantitative approach with a correlational design was employed, involving 120 child–parent pairs selected through purposive sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability, complemented by brief observations of children’s social behavior in the school environment. Data were analyzed using descriptive statistics and simple linear regression. The results showed a positive and significant influence of the parental role on children’s social interaction, with a contribution of 31.7%. These findings reinforce the position of the family as the primary socialization environment in shaping children’s communication, cooperation, empathy, and social adaptation skills, and contribute to strengthening ecological developmental theory and parenting practices based on parental involvement. The practical implications highlight the importance of improving the quality of family communication and enhancing school–parent partnerships to sustainably support children’s social development.